COLLOCATIONAL BEHAVIOR OF “HEAD” IN ENGLISH AND UZBEK: A CORPUS-BASED QUANTITATIVE ANALYSIS - Hafizov Sarvar Boborajab ugli (Bright Mind Publishing, 2025)
The article aims to explore the collocational behavior of the noun “head” in English and its equivalent “bosh” in Uzbek through a comparative corpus-based approach. The study identifies frequent collocates, analyzes grammatical patterns, and highlights cultural and semantic differences by drawing on the British National Corpus and the Uzbek National Corpus. While both languages use “head” or “bosh” in domains such as leadership, emotion, and gesture, structural and idiomatic variations reveal important linguistic and cultural nuances. These findings contribute to translation studies, lexicography, and bilingual language pedagogy.
Keywords: Collocation, corpus linguistics, head, bosh, phraseology, comparative analysis, Uzbek, English.